Transient expression of rabies virus G-glycoprotein using BHK-21 cells cultured in suspension - Nuñez, Eutimio Gustavo Fernández [UNESP]; De Rezende, Alexandre GonÇalves; Puglia, Ana Lia Pradella; Leme, Jaci; Boldorini, Vera Lucia Lopes; Caricati, Celso Pereira; Tonso, Aldo (Springer Nature, 2015)
Objective To assess the expression of rabies virus G-glycoprotein (RVGP) expression using Semliki Forest virus as a vector in combination with BHK-21 cells cultured in suspension. Results A multilevel factorial design was used to quantify effects of temperature (33–37 C), fresh medium addition after the viral adsorption step (100–200 % with respect to the initial cell suspension volume before infection) and harvest time (8–40 h) on RVGP production. Experimental runs were performed in 24-well cell culture plates at a multiplicity of infection (MOI) of 16. An additional experiment in spinner-flask was performed at MOI of 9, using the optimal conditions determined in cell culture plates. Values for temperature, fresh medium addition and harvest time of 33 C, 100 % and 16 h, respectively, ensured the optimal RVGP production in culture plates. The volumetric yield (239 ng ml-1 ) in these conditions was higher than that reported previously for adherent cell culture. In spinner-flasks, the volumetric yield was improved (559 ng ml-1 ). Conclusion These results establish the basis for designing bioprocess to produce RVGP.
Keywords: Bioprocess engineering; Mammalian cells; Viruses; Semliki; Forest virus; Rabies virus; G-glycoprotein